2016
DOI: 10.1038/srep26258
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic strengthening effect of nanocrystalline copper reinforced with carbon nanotubes

Abstract: In this study, a novel multi-walled carbon nanotubes reinforced nanocrystalline copper matrix composite with super high strength and moderate plasticity was synthesized. We successfully overcome the agglomeration problem of the carbon nanotubes and the grain growth problem of the nanocrystalline copper matrix by combined use of the electroless deposition and spark plasma sintering methods. The yield strength of the composite reach up to 692 MPa, which is increased by 2 and 5 times comparing with those of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…The strengthening efficiency is generally used to characterise the strengthening effect of reinforcement. The strengthening efficiency of yield strength was determined by R  = ( σ yc − σ ym )/( V G σ ym )16. The calculated data is also compared with the experimental results of CNTs contained Mg matrix composites in the open publications17181920212223.…”
Section: Resultsmentioning
confidence: 99%
“…The strengthening efficiency is generally used to characterise the strengthening effect of reinforcement. The strengthening efficiency of yield strength was determined by R  = ( σ yc − σ ym )/( V G σ ym )16. The calculated data is also compared with the experimental results of CNTs contained Mg matrix composites in the open publications17181920212223.…”
Section: Resultsmentioning
confidence: 99%
“…Many researches have shown that a close interface can be established between MWCNTs and matrix through the surface of MWCNTs modified by various oxygen-containing functional groups such as carboxyl (-COOH), hydroxyl (-OH), and atomic oxygen (-O) [22,25,26]. They also found O atoms have a beneficial effect on the interface strength at the interface between the MWCNTs and the metal [22,[27][28][29]. However, the function and chemical structure of O atoms at the atomic level are still not really proved [30,31].…”
Section: Distribution Of O Atoms and Its Effect On Mechanical Propertmentioning
confidence: 99%
“…The Ni-CNT composites are usually fabricated by coating in order to make a thin film, via powder metallurgy (PM) process or mixing process and then combine with sintering to obtain the bulk samples. The aim of these processes is offering the possibility of obtaining uniform parts and reducing production costs [5][6][7][8]. Up to now, many authors have attempted to develop new ways for synthesizing Ni-CNT nanocomposites due to their excellent enhanced not only mechanical properties, but also thermal properties, electrical conductivity and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%